-8x+5-4(x-1)=-4x(7x-4)+4

Simple and best practice solution for -8x+5-4(x-1)=-4x(7x-4)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+5-4(x-1)=-4x(7x-4)+4 equation:



-8x+5-4(x-1)=-4x(7x-4)+4
We move all terms to the left:
-8x+5-4(x-1)-(-4x(7x-4)+4)=0
We multiply parentheses
-8x-4x-(-4x(7x-4)+4)+4+5=0
We calculate terms in parentheses: -(-4x(7x-4)+4), so:
-4x(7x-4)+4
We multiply parentheses
-28x^2+16x+4
Back to the equation:
-(-28x^2+16x+4)
We add all the numbers together, and all the variables
-(-28x^2+16x+4)-12x+9=0
We get rid of parentheses
28x^2-16x-12x-4+9=0
We add all the numbers together, and all the variables
28x^2-28x+5=0
a = 28; b = -28; c = +5;
Δ = b2-4ac
Δ = -282-4·28·5
Δ = 224
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{224}=\sqrt{16*14}=\sqrt{16}*\sqrt{14}=4\sqrt{14}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-28)-4\sqrt{14}}{2*28}=\frac{28-4\sqrt{14}}{56} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-28)+4\sqrt{14}}{2*28}=\frac{28+4\sqrt{14}}{56} $

See similar equations:

| 3(b+3)-4(-2+b=19 | | 9-7x-6-7x=6 | | (3x-2)^2-144=0 | | (3x-2)-144=0 | | 3√1000x÷300=10 | | 0.1d-(1/2+d)=2d-7/2d | | 2.x-1=20 | | -3(x-2)/4=x-3/5 | | -2-x+6x=24-x=5 | | 5x+1=-2x+8 | | 4y+2y=3(2y+20) | | 25.5=5x+2 | | 10x-100=9x+81 | | 6x-2(-3x-1)=4(2x+5 | | 5w-4(3w-2)=16-15w | | 7x+3x-5=9x-2x+8 | | 3000+3000-x=5000 | | 4(2x-3)+3=23 | | 8x-2(x+2)=4x+3 | | 10000-x*2=4000 | | 7(x+7)=4(x+2) | | 7+(x/7)=-4 | | X+2*x=30000 | | 15x-11=12x+16=180 | | 8-(12-x)=1 | | 999=(x/2)(1+x) | | 15x-11=12x+16 | | 24x2=20x= | | x^2+6x+14=-3 | | 4/7x=16/5 | | 1=0.02x | | 3/x-12=53 |

Equations solver categories